Talent management practices and librarians performance in academic public libraries Malaysia - Mohd Tumari, Mohd Noor Hasman; Mohamed Shuhidan, Shamila; Mohamad Rosman, Mohamad Rahimi; Baharuddin, Mohammad Fazli (Faculty of Information Management, 2025)
Talent management is crucial for attracting and retaining exceptional staff, ensuring sustainable organizational success. This study aims to identify the level of talent management practices and librarian performance in public universities in Malaysia. The quantitative method approach was used, and 358 librarians were involved. Findings show that the Librarian Performance dimension recorded the highest value of 6.24 and the Job Reward with 5.09 lower value. Suggesting the need for improvement in the aspects of rewards and career development opportunities. Addressing these elements strategically allows libraries to better achieve institutional goals and adapt to evolving educational and research needs.